The effect of corporate social responsibilities on corporate performance: the mediating role of corporate culture and affective commitment - Mohamed Abdulwali, Ali Alsamawi (2021)
Yemen has experienced drastic decline in natural resources (oil and water). Due to the economic distress and social challenges that Yemen is facing, it is very important to understand the complex connection and interdependence of the CSR pillars (economic growth, social development, philanthropy and environmental protection). Corporations can achieve long-term growth by maintaining CSR activities and achieving corporate performance. Furthermore, the area of CSR activities, corporate culture and affective commitment impacting corporate performance, is a relatively unexplored area in the literature. Therefore, the main objective of this research is to examine the direct influence of Yemeni oil and gas companies’ social responsibilities (CSR) activities on their performance as well as the indirect influence on their performance though corporate culture, and affective commitment. A total of 339 employees from three Yemeni oil and gas companies (Safer exploration and Production, Perto-Masila and YLNG.) were drawn from a stratified sample randomly. Adopting the descriptive research design, questionnaires were developed to collect data; the first part covers the demographic information of the respondents and the remaining consists of questionnaires with 42 items, rated on 5-Likert type categories, adapted from established scales which have been validated and used in previous studies. Data were analysed using descriptive statistics, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) procedures. The results indicated that the research instrument was valid and reliable. The study found that both the economic responsibilities and social responsibilities have a direct significant influence on Yemeni oil and gas companies’ performance. However, both the Philanthropic and environmental responsibilities do not have a direct influence on the Yemeni oil and gas companies’ performance. Regarding the indirect impact, three CSR dimensions (economic responsibilities, social responsibilities and Philanthropic responsibilities) have significant indirect effect on the Yemeni oil and gas companies’ performance through corporate culture and affective commitment. However, the environmental responsibilities showed insignificant effect on the Yemeni oil and gas companies’ performance through corporate culture and affective commitment. Hence, Yemeni government is advised to develop CSR-related policies tailored to encourage the adoption of CSR practices by companies. Last but not least, theoretical and practical implications of these findings and recommendations were discussed.